Effectiveness of Using Simpora Application for Data Collection of Pre Popda Participants of Central Java Prefecture 2024 - Dimas Abdul Santiko; Gustiana Mega Anggita (Journal Coaching Education Sports, 2024)
The use of SIMPORA in registering participants is a system designed to assist event organizers in managing participant data effectively and efficiently. This study aims to determine the effectiveness of using the SIMPORA application for data collection of Pre POPDA participants in the Central Java Prefecture in 2024. This research uses the D&M IS success model theory by Delone and McLean. The type and method used in this research is descriptive quantitative research. The sample in this study amounted to 42 people with convenience sampling technique. Data collection in this study by distributing surveys using questionnaires and data analysis techniques used descriptive analysis. The results of this study indicate that each indicator is declared very effective, based on the results of the analysis of the effectiveness assessment of each indicator including system quality by 88.2%, information quality by 85.4%, service quality by 85.2%, usage by 85.2%, user satisfaction by 86.1%, net benefits by 86.8%. Based on the results of the above research, it can be concluded that the resulting system is effective. This explains that SIMPORA users in the 2024 Central Java Pre POPDA activities are satisfied with the effectiveness produced by SIMPORA. So that the use of SIMPORA is needed for data collection activities at every sports event.